Dimensi Politik Gerakan Perempuan: Suatu Survey - Machya Astuti Dewi (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2001)
Survey of literature on women movement which takes place in different places in the world shows us that the movement means different things to different group of people. While the survey tells us that political setting highly influencial in shaping the movement, the very political nature of the movement is not necessarily lays in women relationship to the state. The jargon is that